Isolation and Identification of Probiotic Candidate Lactic Acid Bacteria (Lab) from Shrimp Paste (Mysis relicta) Based on 16s rRNA Gene - Rahmat Wahyudi Putra; Resti Fevria (UNIVERSITAS NEGERI PADANG, 2021)
Terasi is one of the fermented product of shrimp or fish which is often used as food seasoning by the people. Terasi is also a source of Lactic Acid Bacteria (LAB) which has the potential as a culture for probiotic starters. Probiotics are dietary supplements containing live microbes that profitable to their hosts. This study aimed to identify probiotic lactic acid bacteria isolated from terasi of shrimp based on the 16S ribosomal ribonucleic acid (rRNA) gene sequence. LAB isolation from terasi was done by pour plate method using selective medium, MRSA (Man Rogosa Sharpe Agar). The identification of LAB in this study used a method of molecular with a marker gene of 16S rRNA. A total of 3 isolates were obtained from the isolation process. All LAB isolates are rod (Basil) positive Gram bacteria, negative catalase. Two isolates (TR 1 and TR 2) were identified as Enterococcus faecalis. While one more isolate (TR 3) were identified as Weissella cibaria.